Modelo propositivo de planejamento e gestão ambiental para o município de Cacheu - Guiné-Bissau/ África ocidental - Correia Junior, Antonio (2023)
In Guinea-Bissau, cities have been growing haphazardly, without worrying about environmental planning and management that bring financial losses to the most vulnerable families, subject to the risk of flooding, collapse of the slopes where the houses are built, as well as facing inadequate disposal of generated waste and lack of basic sanitation. Thus, the objective is to provide subsidies for implementing and developing actions aimed at environmental planning and management, elaborating a propositional model of planning and management for administrative units in Guinea-Bissau, based on the municipality of Cacheu. The theoretical-methodological procedures are based on geoecological analysis, through information and inventory, analyses, diagnosis, and proposal phases. As a final result, the geoecological zoning map will be presented, with the geoecological units, their forms of use and occupation, as well as their problems, limitations, and potentialities, in order to subsidize the strategies of environmental and municipal management. The problem of municipal environmental planning and management must be seen as a way of improving the quality of life of all citizens, and an opportunity to preserve natural resources, thus making it possible to comply with the current legislation in the country.